1970
DOI: 10.1002/pol.1970.150080927
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of the monomer–polymer particle in styrene emulsion polymerization

Abstract: SynopsisA heterogeneous model for the monomer-polymer particle in styrene emulsion polymerization is presented. I n this model, the growing particle consists of an expanding polymer-rich core surrounded by a monomer-rich shell which serves as the major locus of polymerization, This core-shell model was suggested by kinetic studies with continuously uniform latices which showed that the systems of interest were of the Smith-Ewart case I1 type but that the dynamic-as opposed to equilibrium swelling-particle mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(66 citation statements)
references
References 19 publications
2
64
0
Order By: Relevance
“…For vinyl acetate, experimental evidence has also been found that the conversion range ''appears to be most closely related to the (particles) surface area''. [153] Williams and co-workers [154][155][156][157] published a great deal of experimental data showing that during stage two of styrene emulsion polymerization the average molecular weight in the case of monodisperse particles increases contrary to the expected constancy. These results seeded doubts regarding the homogeneity assumption of the Smith-Ewart theory and led to the conclusion that rather core-shell like polymerization happens.…”
Section: Microscopic Modelingmentioning
confidence: 65%
“…For vinyl acetate, experimental evidence has also been found that the conversion range ''appears to be most closely related to the (particles) surface area''. [153] Williams and co-workers [154][155][156][157] published a great deal of experimental data showing that during stage two of styrene emulsion polymerization the average molecular weight in the case of monodisperse particles increases contrary to the expected constancy. These results seeded doubts regarding the homogeneity assumption of the Smith-Ewart theory and led to the conclusion that rather core-shell like polymerization happens.…”
Section: Microscopic Modelingmentioning
confidence: 65%
“…Clearly, the results of this study support the idea of interfacial polymerization, which has been a matter of ongoing discussion for several decades. [24][25][26][27][28][29][30] …”
Section: Resultsmentioning
confidence: 99%
“…Considering monomer-soluble initiators, this may be the case of a monomer layer around a polymer particle [15] or the encapsulation of a non-solvent by a polymer shell (hollow particles). [16,17] Also for this case, an analytical solution is difficult to obtain but the rate coefficients can be easily obtained from BD simulations.…”
Section: Generation Of Radicals In the Shell Onlymentioning
confidence: 99%